Fundamentals of programmable logic controllers, sensors, and communications - Stenerson, Jon (Pearson Prentice Hall, 2004)
Since the programmable logic controller has become an invaluable tool in American industry, this book responds to the substantial need for trained personnel who can program and integrate these devices. LogixPro programming and simulation software is included so that the reader can write and simulate PLC programs.